Perancangan Program Aplikasi Buku Induk untuk SDK 4 Penabur - Steven Martinnus; Dali Santun Naga (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
This Master Book Application Program for SDK 4 Penabur School was created because the previoslly system still manually uses manual administration book. This application was developed with the aim to simplify the process of storing student data and storage of learning results. In addition to makes it easier for staff to look for students data without having to take a long time. This application is done by using System Development Life Cycle (SDLC). Supporting Software such as Adobe Dreamweaver, PHPMyAdmin, Microsoft Word, Microsoft Visio, and Notepad ++. This application is built using PHP Programming languages and SQL database. This application has been tested using user acceptance testing and black box testing. This master book application can already be used in SDK 4 Penabur Jakarta